Application of Multimedia Interactive Learning Based on Educational Games to Increase Motivation & Independence of Science Learning of Elementary School Students: Literature Review - A. Afrinaramadhani Hatta; Shoffan Fatkhulloh (Global Journal Basic Education, 2026)
This study aims to examine the effectiveness of implementing educational game-based interactive multimedia in enhancing junior high school students’ motivation and learning independence in science education. The research employed a literature review method by analyzing 29 relevant scientific articles from national and international journals, selected through a systematic screening process using the PRISMA approach. The analysis focused on the types of multimedia used, research methods employed, and their impacts on students’ motivation and learning independence. The findings indicate that most studies reported significant improvements in students’ learning motivation, engagement, and understanding of science concepts following the implementation of interactive multimedia. Educational game-based and gamified learning media demonstrated a stronger positive impact than conventional media, as they provide engaging, interactive, and enjoyable learning experiences. Furthermore, interactive multimedia encourages students to learn independently through exploratory features, immediate feedback, and flexibility in controlling their learning pace. However, the effectiveness of multimedia implementation is influenced by the type of media used, instructional approaches, teacher readiness, and the learning environment. This study contributes to strengthening the understanding of the importance of technology integration in science education and serves as a reference for the development of more innovative and adaptive learning media at the junior high school level.